Nonlinear finite element analysis of continuous welded rail–bridge interaction: monitoring-based calibration - Strauss, Alfred; Šomodíková, Martina; Lehký, David; Novák, Drahomír; Bergmeister, Konrad (Journal of Civil Engineering and Management, 2018)
Continuous welded rail is of high interest to operators of railway infrastructure facilities because of the reduced maintenance work and better train driving dynamics it offers. However, the application of continuous welded rail, in particular associated with its interaction with the superstructures of e.g. bridges, requires special caution with regard to the rail stresses in the transition area between the structure and the free field. These stresses are not only influenced by thermal deformations of the bridges but also by the clamp systems between the rails and e.g. the bridge. In general, these connectors are represented by spring elements during modelling, which: (a) causes singularities in the stress distributions in the rails, and (b) cannot capture all the mechanical system changes occurring due to loading, thermal effects, etc. The target of this paper is to present an alternative way of modelling the connection between rails and bridge superstructure based on composite materials which can overcome the disadvantages of the spring model. In particular, a nonlinear model of the whole system was developed for ballasted and non-ballasted track. Special attention was paid to the calibration of rail–bridge interaction and boundary conditions using measured data and code specifications. The aim of this study was to use the results of in-situ measurements to analyse the admissible stress in rails due to their interaction with a bridge caused by temperature loading.